Dampak Kegiatan Pengajian Kelompok Yasin dalam Membentuk Akhlak Anggotanya di Jorong Koto Panjang Nagari Koto Baru Kec. IV Nagari - Yuliharka, Marfiga; Murniyetti, Murniyetti (Darul Yasin Al Sys, 2023)
Recitation is a form of da'wah which is considered quite effective in spreading the religion of Islam. This recitation aims to find out what forms of recitation activities are, what the social behavior of recitation members is and what are the solutions in dealing with the social behavior of its members in Jorong Koto Panjang Nagari Koto Baru Krc.IV Nagari. This research is qualitative with a field approach. The main instrument in the research is the researcher himself with data usage techniques used by means of observation, interviews and documentation. The steps to analyze data are data reduction, data presentation, and drawing conclusions. The results of this research are the form of recitation activities of the Yasin group, namely as a place to gain religious knowledge and also to stay in touch, the social behavior of its recitation members is used as a means of comparison within social castes and the solution provided is to provide advice through an approach to remind each other of good things for smooth running. Yasin group recitation activities.